2018
DOI: 10.1002/ecs2.2097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an invasive alien plant on litter decomposition along a latitudinal gradient

Abstract: Abstract. Invasive alien plant effects on ecosystem functions are often difficult to predict across environmental gradients due to the context-dependent interactions between the invader and the recipient communities. Adopting a functional trait-based framework could provide more mechanistic predictions for invasive species' impacts. In this study, we contrast litter decomposition rates among communities with and without the invasive plant Impatiens glandulifera in five regions along a 1600 km long latitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 55 publications
(171 reference statements)
1
47
0
Order By: Relevance
“…In an ecosystem functioning context, these results show that invasion results in a shift of the community trait space towards (leaf) traits related to increased litter decomposability for both species (Kazakou et al , Orwin et al ). A previous study on I. glandulifera did also show that these trait shifts in the native community, quantified as community weighted means, were correlated with the increasing litter decomposition rates following invasion (Helsen et al ), thus illustrating the potential use of trait hypervolume results in an invader impact framework.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In an ecosystem functioning context, these results show that invasion results in a shift of the community trait space towards (leaf) traits related to increased litter decomposability for both species (Kazakou et al , Orwin et al ). A previous study on I. glandulifera did also show that these trait shifts in the native community, quantified as community weighted means, were correlated with the increasing litter decomposition rates following invasion (Helsen et al ), thus illustrating the potential use of trait hypervolume results in an invader impact framework.…”
Section: Discussionmentioning
confidence: 68%
“…Although overlap between the invader and native species in both control and invaded plots increased around 2.5‐fold for the full dataset compared to the average overlap per study region, overlap was still much larger between the invader and NAT I than between the invader and NAT C (61.3% larger for the average hypervolumes per study region, 86.7% larger for the full hypervolume). This result can likely be explained by the relatively uniform species composition of the plant communities invaded by I. glandulifera across the five study regions (Helsen et al ). For R. rugosa , however, sampling across a larger part of its invaded range should be performed to evaluate the generality of the obtained results for this species.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, the average differences between understorey native and non‐native invasive plants in leaf nutrient levels were often not as pronounced as in other ecosystems (Leffler, James, Monaco, & Sheley, ), suggesting that differences between plant growth habitat (i.e., understorey plants and canopy trees in this instance) are a key feature in understanding decomposition dynamics in these forests. This observation highlights that, on average, non‐native and native plants affect decomposition through similar mechanisms, and corroborates that non‐native understorey plants with overlapping green leaf and litter traits are less likely to alter forest decomposition dynamics than those that are functionally unique (Drenovsky et al, ; Finerty et al, ; Funk, Cleland, Suding, & Zavaleta, ; Helsen et al, ). Importantly, however, while the average effects of native and non‐native understorey plants were similar, non‐native understorey species tended to be more functionally unique (i.e., occupy more distant areas of trait space) than native understorey species.…”
Section: Discussionmentioning
confidence: 54%
“…Overall, we found that the mass ratio effect and trait diver- are less likely to alter forest decomposition dynamics than those that are functionally unique (Drenovsky et al, 2012;Finerty et al, 2016;Funk, Cleland, Suding, & Zavaleta, 2008;Helsen et al, 2018). Importantly, however, while the average effects of native and non-native understorey plants were similar, non-native understorey species tended to be more functionally unique (i.e., occupy more distant areas of trait space) than native understorey species.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation